RI 6705 Heat Of Formation Of Scandium Trichloride - J. M. Stuve (The National Institute for Occupational Safety and Health (NIOSH), 1965)
Calorimetric data for the dissolution of scandium sesquioxide and scandium trichloride in 4.360 molal hydrochloric acid were used to evaluate the standard heat of formation of ScCl3(c). The heat of reaction for Sc(c) + 1.5Cl2(g) = ScCl3(c) at 298.15° K was computed as -225,440 ±340 cal/mole.